(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
The main factor in the airline transport service being the reason for the choice is the place and time benefit it provides. Delays are negative situations that disrupt the time utility, reduce airlines’ profits, cause congestion trouble and disrupt tariff plans. The first part of the study consists of information about delays and fundamental issues related to delays. In the second part, it has been tried to summarize the studies on the slot, which is directly related to the delays. In the last part, two airlines that adopted different business models, full-service carrier and low-cost carrier, were compared based on delay reasons. The study aims to determine the causes of delay and their predictive roles comparatively. We have used the multiple hierarchical regression model for this purpose. American Airlines and Southwest Airlines were selected as full-service carrier and low-cost carrier, respectively. We have determined that even though Southwest Airlines is a low-cost carrier, and more punctual than American Airlines, delays stemming from the carrier play a greater role in overall delays than American Airlines.